Development of an IHE MRRT-compliant open-source web-based reporting platform. - Pinto dos Santos, Daniel; Klos, G.; Kloeckner, R.; Oberle, R.; Dueber, C.; Mildenberger, P. (European Radiology, 2017)
Objectives: To develop a platform that uses structured reporting templates according to the IHE Management of Radiology Report Templates (MRRT) profile, and to implement this platform into clinical routine.Methods: The reporting platform uses standard web technologies (HTML / JavaScript and PHP / MySQL) only. Several freely available external libraries were used to simplify the programming. The platform runs on a standard web server, connects with the radiology information system (RIS) and PACS, and is easily accessible via a standard web browser.Results: A prototype platform that allows structured reporting to be easily incorporated into the clinical routine was developed and successfully tested. To date, 797 reports were generated using IHE MRRT-compliant templates (many of them downloaded from the RSNA's radreport.org website). Reports are stored in a MySQL database and are easily accessible for further analyses.Conclusion: Development of an IHE MRRT-compliant platform for structured reporting is feasible using only standard web technologies. All source code will be made available upon request under a free license, and the participation of other institutions in further development is welcome.Key Points: • A platform for structured reporting using IHE MRRT-compliant templates is presented. • Incorporating structured reporting into clinical routine is feasible. • Full source code will be provided upon request under a free license.